2016
DOI: 10.11606/issn.2448-1750.revmae.2016.137349
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de fogueiras e antracologia em contexto Proto-Jê do Sul

Abstract: O estudo de fogueiras Proto-Jê do Sul em sítios do nordeste do RS permitiua compreensão de questões relacionadas à tecnologia de fogueiras e à economiade combustíveis destes grupos. Fez-se isso a partir de uma descrição qualitativa das fogueiras e da análise antracológica do carvão coletado em cada sítio. Encontramos elementos estruturais que operavam sobre a queima, sugerindo um conhecimentoapurado sobre o processo de combustão correlato a seus usos. A análise antracológica permitiu a classificação dos tipos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Fire was used for many things (e.g., heating, cooking, ceramic preparation, and cremation) and may have involved selective extraction or gathering of species for fuel. Fuel for funeral use must reach very high temperatures, for domestic use it must be easily controllable [65]. The use of fire in rituals can also lead to the selection of woods by symbolic characteristics.…”
Section: Plos Onementioning
confidence: 99%
“…Fire was used for many things (e.g., heating, cooking, ceramic preparation, and cremation) and may have involved selective extraction or gathering of species for fuel. Fuel for funeral use must reach very high temperatures, for domestic use it must be easily controllable [65]. The use of fire in rituals can also lead to the selection of woods by symbolic characteristics.…”
Section: Plos Onementioning
confidence: 99%
“…Those fires produced large quantities of wood charcoal, the study of which allows for the reconstruction of past vegetation and landscape and other aspects of human activity. In this article, we discuss evidence of landscapes and wood uses in proto-Jê contexts based on our consideration of some unpublished results and our reinterpretation of previously published data (Azevedo and Scheel-Ybert 2016a, 2016b) in light of the results of more recent research (Robinson, Iriarte, De Souza, Corteletti et al 2017; Robinson, Iriarte, De Souza, Marozzi, and Scheel-Ybert 2017). We present data from four research areas in southern Brazil and Argentina (Figure 1).…”
mentioning
confidence: 85%
“…These archaeological contexts, dated from 1200 ± 40 to 350 ± 40 years BP, cover all the occupation period known to the region. The research was conducted by the first author (Azevedo and Scheel-Ybert 2016a, 2016b) and reported in a master's thesis developed in the Laboratory of Archaeobotany and Landscape of Museu Nacional in Rio de Janeiro (LAP/MN) 1 Figure 2.Proto-Jê archaeological sites in the Pinhal da Serra region, with the studied sites labeled (adapted from Azevedo and Scheel-Ybert 2016b).…”
Section: Pinhal Da Serra Case Studymentioning
confidence: 99%